2018
DOI: 10.1111/jdv.14668
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of regimens in Narrowband UVB and PUVA in early stage mycosis fungoides: position paper from the Italian Task Force for Cutaneous Lymphomas

Abstract: UV-based (PUVA and narrowband UVB) phototherapy is broadly and commonly used in the treatment of Cutaneous T-cell Lymphomas (CTCL), yet unfortunately, the evidence for the efficacy of these treatments is based only on case series or prospective but non-randomized studies. Therefore, no internationally approved guidelines exist and no standardization of schedules has been proposed. Recently, consensus guidelines have been published by the United States Cutaneous Lymphoma Consortium. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…Currently, data regarding the role of skin phototype in the clinical response to NB-UVB phototherapy is contradictory. Studies on early lymphoproliferative disorders have stated that phototypes I-II may require lower total cumulative dose to show clinical response (Grandi et al, 2018). In our study 7 patients with skin phototype III-IV reached 50-90% BSA clearance with a range of 9-50 sessions, indicating they may also show a rapid response to low phototherapy doses.…”
Section: Dear Editorsupporting
confidence: 49%
“…Currently, data regarding the role of skin phototype in the clinical response to NB-UVB phototherapy is contradictory. Studies on early lymphoproliferative disorders have stated that phototypes I-II may require lower total cumulative dose to show clinical response (Grandi et al, 2018). In our study 7 patients with skin phototype III-IV reached 50-90% BSA clearance with a range of 9-50 sessions, indicating they may also show a rapid response to low phototherapy doses.…”
Section: Dear Editorsupporting
confidence: 49%
“…Whilst there are no direct head-to-head controlled trials of NB-UVB and PUVA for early stage CTCL, both have been shown to be effective for this stage of disease ( 5 , 64 ). In one retrospective study 81% of patients with early stage CTCL achieved complete remission with NB-UVB, compared with 71% with PUVA ( n = 56) ( 65 ).…”
Section: Cutaneous T-cell Lymphomamentioning
confidence: 99%
“…Photopheresis may of course be required for Sezary syndrome ( 71 , 72 ). Thus, in summary NB-UVB for early stage disease and PUVA for plaque stage disease as monotherapy or in combination therapy for more advanced disease should be considered as mainstays in management ( 5 , 64 , 73 ).…”
Section: Cutaneous T-cell Lymphomamentioning
confidence: 99%
“…UVA penetrates the entire dermis and possibly the subcutaneous tissue. Therefore, PUVA represents a good therapeutic option for plaque stage disease (up to 85% of patients with stage IA experienced complete response) (4,11,12). Complete response rates were slightly lower in patients treated with NB-UVB (54% to 90%) (4).…”
Section: Discussionmentioning
confidence: 99%
“…Questions regarding the efficacy of maintenance phase are still debated (4). Studies comparing recurrence rates in patients who received maintenance phase and those who underwent follow-up are scarce including a relatively small proportion of patients with dark phototype (phototypes IV-VI) (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%